The Thai Translation of the Biography of Kang Senghui in the Gaoseng zhuan (2): Retribution for Sun Hao’s Disparaging Acts against the Buddha Image - Pitakteeradham, Maythee; Wongwarangkool, Piyaphon; Srimork, Phonpimol (Journal of Buddhist Studies Chulalongkorn University, 2022)
The Gaoseng zhuan, or Lives of Eminent Monks, written around 530 A.D. by the monk Huijiao, is one of the most important works dealing with the history of Chinese Buddhism from 67-519 A.D. The scripture contains 257 biographies of prominent monks as well over 200 biographies of subordinate monks and upasakas. These biographies are divided into ten categories, the first of which – the one that contains 35 biographies of great contributors to translating the Sutra – Huijiao placed great emphasis on. The authors attempt to study one of the figures in this category, i.e. Kang Senghui, who lived in the Three Kingdoms period. Kang Senghui’s biography was detailed in the periods of two different rulers: 1) during the reign of Sun Quan, and 2) during the reign of Sun Hao. In this paper, the authors focus on the study and translation of Kang Senghui’s biography during the reign of Sun Hao. The study finds that Kang Senghui faced a crisis because the court sought to suppress Buddhism which was slighted by Sun Hao. As a retribution for his disparaging acts against the Buddha Image, Sun Hao opened his mind to listen to Kang Senghui's sermon about the Law of Karma. He eventually became a supporter of Kang Senghui and Buddhism.